"We reaffirm our Mozambican identity in the fight against HIV and AIDS": Examining educational perspectives on women's 'proper' place in the nation of Mozambique. Issue 1 (March 2015) - Miedema, Esther; Millei, Zsuzsa
There is increasing recognition of the importance of space in the study of education, resulting in a greatly diversified literature on the geographies of education. This article builds on this growing body of scholarly work to examine a number of critical spatial assumptions underpinning school-based HIV- and AIDS-related education in Maputo, Mozambique. It does so through an analysis of key governmental and ministerial documents and policy-makers' and educators' conceptions of the aims of such education. This article highlights how school-based HIV- and AIDS-related education in Mozambique was conceptualized in gendered and distinctly place-based terms. In addition, we elucidate how, despite the various discursive shifts since the struggle for independence from Portugal, young women continue to be construed as the symbolic anchor of the nation, their natural place defined in relation to the domestic, the intimate, and local 'in-here.'